Developing Undergraduate Critical Thinking Skills in Mechanics through the Use of Case Method-Based Teaching Materials with QR Code Videos - Defianti, Aprina; Sutarno, Sutarno; Johan, Henny (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This research aims to evaluate the effectiveness of using case method-based teaching materials with QR code videos on undergraduate students' critical thinking skills in mechanics. This research used a quasi-experimental method with a post-test-only control group design. A sample of 2 classes was taken using a purposive sampling technique. The experimental class used case method-based mechanics teaching materials and videos in QR codes, while the control class used print-outs of material summaries. Data collection was carried out through observation and critical thinking skills tests. Critical thinking skills test results data were analyzed using descriptive and inferential statistics. The t-test of two independent non-homogeneous samples is used to test the hypothesis of differences in means. The t-test results showed a difference in the average critical thinking skills scores of experimental and control class students with , greater than at (rounded up to 43). Based on these results, using case method-based mechanics teaching materials and videos in QR codes effectively develops students' critical thinking skills with an effectiveness level of 0.82, which means highly influential.